Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
For Business Enquiry


Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number


Mon to Sat - 11 AM to 8 PM

Plz....solve quickly......board is up...

Asked by 12th March 2009, 11:59 AM
Answered by Expert

tsum of the zeroes is  given by

sum of the zeroes =-b/a


 product of the zeroes=c/a

So, in this case,

sum of zeroes=2a=-1/3...(i)


 product of the zeroes==1/3

equation (i) gives you a=-1/6

substitute this value in theproduct of the zeroes equation and get b.


Answered by Expert 12th March 2009, 12:23 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp